Some investigative and scientific research results on medicinal plant resources in the Xuan Son national park, Phu Tho province - Tuan, Nguyen Anh; Hoi, Tran Minh; On, Tran Van (Academia Journal of Biology, 2012)
The Xuan Son national park is one of the medicinal plants - diverse national parts in Vietnam. 665 species, which belong to 6 phylum, 139 families, 298 genera of vascular plant, has recorded in the field surveys. Among them, 22 species are listed in Red Data Book of Vietnam, 22 species in Red List of Medicinal plants of Vietnam and 3 species in Governmental Decree 32/2006/ND-CP. Among 139 families, the 10 most useful ones are Euphorbiaceae, Fabaceae, Rubiaceae, Moraceae, Verbenaceae, Menispermaceae, Myrsinaceae, Zingiberaceae and Araliaceae. Among 298 genera, the 12 most useful ones are Ficus, Ardisia, Polygonum, Alpinia, Limnophila, Stephania, Hedyotis, Mallotus, Desmodium, Piper, Solanum and Psychotria. The six popular types of medicinal plants in Xuan Son national park are tree (17.45%), shrub (22.26%), climber (25.86%), herb (31.88%), epiphytes (1.8%) and parasite (0.75%), distributing mainly to the primary forest, the secondary forest and moorland. This natural resource plays a vital part in community healthcare actions. It is used by local people to treat many diseases as: fever, marsh fever, cold, colic, diarrhea, cough, asthma… and to foster strength. The medicinal plant resource in Xuan Son national part has an important economical value and a potentiality to develop new pharmaceutical and other natural products, contributing to form the cultural identity of ethnic community in the area.